Binder for iron powder production
By combining the active components of the composite binder, chitosan microspheres, and polyacrylic acid, the problems of low initial strength and residual inorganic impurities in cold-pressed iron powder pellets were solved, achieving high-strength and low-impurity pellet performance.
Patent Information
- Application Number
- CN202511280274.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-09-09
AI Technical Summary
Existing iron powder binders have low strength and leave a lot of inorganic impurities in the early stage of cold-pressed pellets, which affects the quality of the pellets and makes it difficult to meet the needs of practical applications.
The active components of the composite binder, including chitosan microspheres and polyacrylic acid, are used to improve the initial structural stability of cold-pressed pellets through chemical bonding and physical entanglement, and decompose into carbon sources during the heat treatment stage to reduce the impact of inorganic impurities.
It improves the initial strength and stability of cold-pressed pellets after heat treatment, reduces the impact of inorganic impurities on pellet grade, and meets the needs of practical applications.
Smart Images

Figure CN120796699A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of iron powder binder, more particularly, it relates to a kind of binders for iron powder production. BACKGROUND
[0002] In the iron powder smelting process, in order to improve the physical properties of raw materials and subsequent processing efficiency, the iron powder usually needs to be cold-pressed, and the loose iron powder particles are compressed into a group by mechanical pressure, which creates favorable conditions for subsequent reduction or smelting process.
[0003] Iron powder cold-pressed processing stage needs to add binder, which firmly combines iron powder particles through the binding effect to form a stable pellet structure. The commonly used iron powder binder in industry is divided into organic binder and inorganic binder. In inorganic binder, sodium silicate has obvious advantages due to its high temperature resistance and excellent wetting performance. When used, sodium silicate solution spreads on the surface of iron powder particles, and through the action of physical adsorption layer and other effects, the binding effect on iron powder is realized. However, this binding effect depends on the cross-linking of sodium silicate hydrolysis, and the cold-pressed forming environment limits the cross-linking reaction of sodium silicate to some extent, resulting in that the initial strength of the cold-pressed pellets prepared by using sodium silicate binder is generally low, and the prepared cold-pressed pellets are prone to breakage.
[0004] The Chinese patent application file with the publication number CN105219956A discloses a preparation method of a composite binder for iron powder cold-pressed pellets. In the scheme, silicate binder is matched with pre-gelatinized starch and other organic components, and additives are added and mixed to improve the binding strength of cold-pressed iron powder pellets through the combined effect. At the same time, due to the removable characteristics of organic components in subsequent heat treatment, the grade of pellets can be improved.
[0005] In the above scheme, although the binding strength of the pellets can be improved by matching the components of the composite binder, the blending form is difficult to play the combined effect of improving the initial binding strength of the pellets, and since the inorganic components introduced in the binder components remain more, they will still have a great impact on the grade of the pellets, so it is necessary to find a binder formula for iron powder that can improve the initial binding strength of cold-pressed pellets and reduce the introduction of inorganic impurities. SUMMARY
[0006] In order to further improve the initial binding strength of cold-pressed pellets and reduce the residual inorganic impurities of the binder, the present application provides a binder for iron powder production, which adopts the following technical scheme: A binder for iron powder production is prepared by mixing the following raw materials: 50-70 parts of binder active component, 20-30 parts of water, 5-8 parts of ammonium dihydrogen phosphate, and 3-5 parts of sodium carboxymethyl cellulose; wherein the preparation steps of the binder active component include the following: [S01] Take the pre-liquid, mix with chitosan microspheres, reduce pressure defoaming treatment, then restore normal pressure, after standing take the solid part, disperse with oily sealant, then add acid stirring treatment, after standing again low speed centrifugation, take the bottom layer of precipitation, after washing and drying to get the composite product; [S02] Take the composite product, add mixed solvent, disperse, warm up and pass nitrogen, then first add acrylic monomer, add crosslinking agent, react, then supplement acrylic monomer, initiate treatment, then adjust the pH to 7, filter to take the precipitate part, after washing and drying to get the bonding active component; The pre-liquid is obtained by water treatment of sodium silicate, aluminum silicate, borax and sodium hydroxide.
[0007] By adopting the above technical scheme, the bonding active component can play a bonding effect in the cold-pressed pellet forming and subsequent heat treatment stage. The bonding active component is prepared by combining the composite product with polyacrylic acid grafting; wherein the composite product is obtained by reacting the "water-in-oil" emulsion of chitosan with epichlorohydrin to obtain chitosan microspheres, and the microspheres are further embedded in the pre-liquid under reduced pressure and sealed. The pre-liquid in the chitosan microspheres is mainly composed of the hydration solution of sodium silicate, which is used to maintain the stability of the pellets during hot melting. In use, the outer layer of polyacrylic acid in the bonding active component is combined with the oxide layer on the surface of the iron powder through hydrogen bonding and covalent bonding, and its growing chain structure can penetrate into the gap between the iron powder particles. Finally, through chemical bonding and physical entanglement, the stability of the initial structure of the cold-pressed pellets is improved; during the subsequent heat treatment of the cold-pressed pellets, the sealing structure of the bonding active component collapses in the initial heating stage, the pre-liquid embedded in the chitosan microspheres rapidly leaks along the microsphere channels and rapidly condenses into a network under the action of heat, thereby maintaining the stability of the structure of the cold-pressed pellets during heat treatment; as the heating continues, the organic matter in the bonding active component is decomposed into carbon components, which can provide a carbon source for the heat treatment of the pellets and escape with the hot melting tail gas during the process, reducing the impact of the bonding component on the grade of the cold-pressed pellets.
[0008] Preferably, in the step [S01], the preparation step of the chitosan microspheres includes the following: take chitosan solution, water bath treatment, then add n-hexane, high-speed shearing treatment, then drop 10% mass concentration of epichlorohydrin, react, then after leaching, low-temperature centrifugation to obtain chitosan microspheres.
[0009] The chitosan solution is obtained by mixing chitosan, deionized water and glacial acetic acid according to a mass-volume ratio of (0.8-1) g:100 ml:(0.5-0.7) ml; The deacetylation degree of the chitosan is 50%; The volume ratio of the chitosan solution, n-hexane and 10% mass concentration of epichlorohydrin used is 100:(70-80):(10-12); The high-speed shearing treatment operation is: adjusting the rotating speed to 5000-8000 rpm, and treating for 15-25 min. The leaching and low-temperature centrifugal treatment is: adding anhydrous ethanol with a volume of five times that of the chitosan solution into the solution, treating for 3-5 h, then adjusting the temperature to 3-4 ℃, adjusting the centrifugal speed to 3000-5000 rpm, and treating for 10-20 min.
[0010] By adopting the above technical scheme, the chitosan solution is used as the water phase, and n-hexane is used as the oil phase, and after high-speed shearing emulsification, an emulsion with a "water-in-oil" structure can be obtained; the subsequent epoxy chloropropane diffuses through the oil phase and reacts with the functional groups such as amino groups on the chitosan dispersed in the water phase to form a cross-linked network, and finally the spherical chitosan is obtained; the addition of anhydrous ethanol for leaching treatment can remove the oil phase part and unreacted impurities through solvent replacement, and the subsequent low-temperature auxiliary treatment can further promote the formation of the cavity structure.
[0011] Preferably, in the step [S01], the reduced-pressure defoaming treatment is: reducing the pressure in the container to 0.1-0.3 MPa, adjusting the magnetic stirring speed to 75 rpm, and treating for 3-4 h. The oil sealing agent is obtained by mixing white mineral oil, n-hexanol and Tween-20 according to the mass-volume ratio of (40-50) ml:10 ml:(0.5-1) g. The acid addition and stirring treatment is: adding 0.05 mol / L hydrochloric acid at a speed of 1-1.5 ml / min, adjusting the magnetic stirring speed to 50 rpm, and stopping stirring after stirring for 40-60 min.
[0012] By adopting the above technical scheme, the chitosan cavity structure is used to embed the pre-liquid and the post-sealing treatment. The pre-liquid is supplemented to the cavity under the action of the ambient pressure by adjusting the reduced-pressure defoaming conditions; then the oil sealing agent is used to form an oil protective layer temporarily around the chitosan microspheres, so as to avoid the pre-liquid from overflowing from the cavity structure in the treatment process; the subsequent addition of the acid solution further treats the sodium silicate in the pre-liquid on the surface of the chitosan microspheres, so as to promote the cross-linking and sealing of the sodium silicate.
[0013] Preferably, in the step [S02], the mixed solvent is obtained by mixing ethanol and acetic acid with a mass concentration of 0.5% according to the volume ratio of (0.5-1):1. The cross-linking agent is obtained by mixing cerium ammonium nitrate and ethylenediaminetetraacetic acid with a mass concentration of 3% according to the mass-volume ratio of (0.2-0.3) g:(1-1.2) ml. The mass ratio of the composite product, the first addition of the acrylic monomer and the additional acrylic monomer is (10-15):1:(5-6).
[0014] By adopting the technical scheme, the growing chain structure of polyacrylic acid can be obtained on the surface of the chitosan microspheres. Under the action of the crosslinking agent, the small amount of acrylic acid monomer added first can be reacted with the chitosan through an initiation reaction to realize preliminary compounding; the subsequent acrylic acid monomer added additionally continues to react, and finally the growing chain of polyacrylic acid is obtained on the chitosan microspheres.
[0015] In summary, the present application has the following beneficial effects: 1. In the present application, the composite product is preferably grafted with polyacrylic acid to obtain a binder active component; during the cold pressing of the iron powder into a ball, the outer layer of polyacrylic acid of the composite product can improve the stability of the initial structure of the cold pressed ball through bonding and physical entanglement; and during the heat treatment of the cold pressed ball, the organic component in the binder active component is decomposed into carbon-containing substances to provide a carbon source for the reduction of the iron powder, and is volatilized with the hot melt tail gas in the process, thereby reducing the influence of the introduction of the binder on the grade of the cold pressed ball.
[0016] 2. In the present application, the chitosan microspheres with a cavity structure are obtained through the emulsion polymerization reaction of epichlorohydrin and chitosan, and then the pre-liquid is embedded in the cavity through processing; during the initial heating of the heat treatment of the cold pressed ball, the pre-liquid in the microspheres leaks, and is rapidly condensed into a net to wrap the ball powder under the action of heat, thereby maintaining the stability of the overall structure of the cold pressed ball.
[0017] 3. The cold pressed ball prepared by using the binder for iron powder production according to the present application has a ball drop strength of >7.6 times, a green ball compressive strength of >41.2 daN, and a mature ball compressive strength of >238.8 daN, thereby meeting the requirements of practical application. BRIEF DESCRIPTION OF DRAWINGS
[0018] Figure 1 The SEM scanning test results of the chitosan microspheres according to the scheme of Example 2 of the present application.
[0019] Figure 2 The ball drop strength test results of the test samples of Examples 1-5 and Comparative Examples 1-2 of the present application.
[0020] Figure 3 The green ball / mature ball compressive strength test results of the test samples of Examples 1-5 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0021] Preparation Example 1 Take 100 ml chitosan solution, adjust the magnetic stirring speed to 100 rpm, under the condition of 40℃ water bath for 2h, then mixed with 70 ml n-hexane, using high speed emulsifier to adjust the speed 5000 rpm, 15 min, then slowly add 10 ml of 10% mass concentration of epichlorohydrin solution to the system at a speed of 2 ml / min, re-adjust the magnetic stirring speed to 50 rpm, after 5h reaction, add 500 ml of absolute ethanol for further treatment for 3h, then reduce the system temperature to 3℃, adjust the centrifugal speed to 3000 rpm for 10 min, then take the bottom layer precipitate, washed with absolute ethanol for 3 times, vacuum dried at 35℃ to obtain chitosan microspheres.
[0022] Take 60 g sodium silicate, 15 g aluminum silicate, 3 g borax, 0.3 g sodium hydroxide and 22.5 g deionized water, adjust the magnetic stirring speed to 250 rpm, treat for 5 min, then add 7.5 g chitosan microspheres, reduce the pressure of the container to 0.1 MPa, adjust the magnetic stirring speed to 75 rpm, treat for 3h, then restore the normal pressure, and stand for another 3h, then take the solid part and add it to 50 ml of oil sealant, adjust the magnetic stirring speed to 100 rpm, stir for 5 min, reduce the stirring speed to 50 rpm, add 10 ml of 0.05 mol / L hydrochloric acid to the system at a speed of 1 ml / min, stir for 40 min, then stop stirring, stand for 30 min, then adjust the centrifugal speed to 1000 rpm for low speed centrifugation, take the bottom layer precipitate, alcohol wash for 2 times, then stand overnight at room temperature, dry to obtain the composite product.
[0023] The chitosan solution is obtained by mixing chitosan (50% deacetylation degree), deionized water and glacial acetic acid in a mass-volume ratio of 0.8 g:100 ml:0.5 ml. The oil sealant is obtained by mixing white mineral oil, n-hexanol and Tween-20 in a mass-volume ratio of 40 ml:10 ml:0.5 g.
[0024] Preparation Example 2 Take 100 ml chitosan solution, adjust the magnetic stirring speed to 100 rpm, under the condition of 40℃ water bath for 2h, then mixed with 70 ml n-hexane, using high speed emulsifier to adjust the speed 5000 rpm, 15 min, then slowly add 10 ml of 10% mass concentration of epichlorohydrin solution to the system at a speed of 2 ml / min, re-adjust the magnetic stirring speed to 50 rpm, after 5h reaction, add 500 ml of absolute ethanol for further treatment for 3h, then reduce the system temperature to 3℃, adjust the centrifugal speed to 3000 rpm for 10 min, then take the bottom layer precipitate, washed with absolute ethanol for 3 times, vacuum dried at 35℃ to obtain chitosan microspheres.
[0025] Take 75 g of sodium silicate, 16 g of aluminum silicate, 4 g of borax, 0.4 g of sodium hydroxide and 25 g of deionized water, adjust the magnetic stirring speed to 300 rpm, treat for 15 min, then add 8 g of chitosan microspheres, reduce the pressure of the container to 0.2 MPa, adjust the magnetic stirring speed to 75 rpm, treat for 4 h, then restore the normal pressure, and stand for 3 h, then take the solid part, add it to 50 ml of oil sealing agent, adjust the magnetic stirring speed to 100 rpm, treat for 10 min, reduce the stirring speed to 50 rpm, add 10 ml of 0.05 mol / L hydrochloric acid to the system at a speed of 1.2 ml / min, stir for 60 min, then stop stirring, stand for 30 min, then adjust the centrifugal speed to 1000 rpm for low speed centrifugation, take the bottom precipitate, wash with alcohol for 3 times, stand overnight at room temperature, dry to obtain the composite product.
[0026] The chitosan solution is obtained by mixing chitosan (degree of deacetylation of 50%), deionized water and glacial acetic acid according to a mass-volume ratio of 1 g:100 ml:0.6 ml. The oil sealing agent is obtained by mixing white mineral oil, n-hexanol and Tween-20 according to a mass-volume ratio of 45 ml:10 ml:0.75 g.
[0027] Preparation Example 3 Take 100 ml of chitosan solution, adjust the magnetic stirring speed to 100 rpm, treat for 3 h under the condition of 50℃ water bath, then mix with 80 ml of n-hexane, use a high-speed emulsifier to adjust the rotating speed to 8000 rpm, treat for 25 min, then slowly add 12 ml of 10% mass concentration of epoxy chloropropane solution to the system at a speed of 3 ml / min, adjust the magnetic stirring speed to 50 rpm, react for 8 h, then add 500 ml of anhydrous ethanol and continue to treat for 5 h, then reduce the temperature of the system to 4℃, adjust the centrifugal speed to 5000 rpm and treat for 20 min, then take the bottom precipitate, wash with anhydrous ethanol for 3 times, and dry at 35℃ under vacuum to obtain chitosan microspheres.
[0028] Take 90 g of sodium silicate, 18 g of aluminum silicate, 4.5 g of borax, 0.45 g of sodium hydroxide and 30 g of deionized water, adjust the magnetic stirring speed to 300 rpm, treat for 20 min, then add 8 g of chitosan microspheres, reduce the pressure of the container to 0.3 MPa, adjust the magnetic stirring speed to 75 rpm, treat for 4 h, then restore the normal pressure, and then take the solid part, add it to 50 ml of oil sealing agent, adjust the magnetic stirring speed to 100 rpm, stir for 10 min, reduce the stirring speed to 50 rpm, add 10 ml of 0.05 mol / L hydrochloric acid to the system at a speed of 1.5 ml / min, stir for 60 min, then stop stirring, stand for 30 min, then adjust the centrifugal speed to 1000 rpm for low speed centrifugation, take the bottom precipitate, alcohol wash 3 times, and then place at room temperature overnight, dry to obtain the composite product.
[0029] The chitosan solution is obtained by mixing chitosan (degree of deacetylation 50%), deionized water and glacial acetic acid in a mass-volume ratio of 1 g:100 ml:0.7 ml. The oil sealing agent is obtained by mixing white mineral oil, n-hexanol and Tween-20 in a mass-volume ratio of 50 ml:10 ml:1 g.
[0030] Example 1 In this example, the preparation steps of the binder active component are as follows: Take 50 g of the binder active component, 20 g of deionized water, 5 g of ammonium dihydrogen phosphate and 3 g of sodium carboxymethyl cellulose, adjust the magnetic stirring speed to 100 rpm, treat for 5 min, and then obtain.
[0031] In this example, the preparation steps of the binder active component are as follows: Take 5 g of the composite product, add 50 ml of mixed solvent, immediately adjust the magnetic stirring speed to 100 rpm, treat for 5 min, then increase the system temperature to 45℃, exhaust the air with nitrogen, add 0.5 g of acrylic acid monomer and 0.2 g of cerium nitrate to the system, then add 1 ml of 3% ethylenediaminetetraacetic acid dropwise at a rate of 1 ml / min, treat for 1 h, then add 2.5 g of acrylic acid monomer to the system, add 0.1 g of methylene bisacrylamide and 0.1 g of ammonium persulfate, adjust the temperature to 50℃, treat for 2 h, then adjust the pH to 7 with 0.1 mol / L sodium hydroxide solution, filter the precipitate, wash with water for 2 times, and then dry in an oven at 35℃ for 3 h to obtain the binder active component.
[0032] The composite product in this example is prepared by Preparation Example 1.
[0033] The mixed solvent is obtained by mixing ethanol and 0.5% acetic acid in a volume ratio of 0.5:1.
[0034] Example 2 In this example, the preparation steps of the binder for iron powder production are as follows: Take 60g of the binder active component, 25g of deionized water, 5g of ammonium dihydrogen phosphate, and 4g of sodium carboxymethyl cellulose, mix them, adjust the magnetic stirring speed to 200rpm, and process for 10min. Then you get it.
[0035] In this example, the preparation steps of the binder active component are as follows: Take 6g of the composite product, add 50ml of the mixed solvent, adjust the magnetic stirring speed to 100rpm immediately, process for 5min, then raise the system temperature to 45℃, exhaust the air with nitrogen, add 0.5g of acrylic monomer and 0.25g of cerium ammonium nitrate to the system, then add 1ml of 3% ethylenediaminetetraacetic acid dropwise at a rate of 1ml / min, process for 1.5h, then add 2.5g of acrylic monomer to the system, add 0.1g of methylene bisacrylamide and 0.1g of ammonium persulfate, adjust the temperature to 50℃, process for 2h, then adjust the pH to 7 with 0.1mol / L sodium hydroxide solution, filter the precipitate, wash it twice with water, and dry it in an oven at 35℃ for 3h to obtain the binder active component.
[0036] The composite product in this example is prepared according to Preparation Example 2.
[0037] The mixed solvent is obtained by mixing ethanol and 0.5% acetic acid with a volume ratio of 1:1.
[0038] Example 3 In this example, the preparation steps of the binder for iron powder production are as follows: Take 65g of the binder active component, 30g of deionized water, 7g of ammonium dihydrogen phosphate, and 5g of sodium carboxymethyl cellulose, mix them, adjust the magnetic stirring speed to 300rpm, and process for 15min. Then you get it.
[0039] In this example, the preparation steps of the binder active component are as follows: Take 7.2g of the composite product, add 50ml of the mixed solvent, adjust the magnetic stirring speed to 100rpm immediately, process for 5min, then raise the system temperature to 50℃, exhaust the air with nitrogen, add 0.5g of acrylic monomer and 0.3g of cerium ammonium nitrate to the system, then add 1.1ml of 3% ethylenediaminetetraacetic acid dropwise at a rate of 1ml / min, process for 1.5h, then add 3g of acrylic monomer to the system, add 0.1g of methylene bisacrylamide and 0.15g of ammonium persulfate, adjust the temperature to 60℃, process for 2.5h, then adjust the pH to 7 with 0.1mol / L sodium hydroxide solution, filter the precipitate, wash it twice with water, and dry it in an oven at 35℃ for 3h to obtain the binder active component.
[0040] The composite product in the present example is prepared by Preparation Example 3.
[0041] The mixed solvent is obtained by mixing ethanol and acetic acid with a mass concentration of 0.5% in a volume ratio of 0.5:1.
[0042] Example 4 In the present example, the preparation steps of the binder for iron powder production are as follows: Take 70g of the binder active component, 30g of deionized water, 8g of ammonium dihydrogen phosphate, and 5g of sodium carboxymethyl cellulose, adjust the magnetic stirring speed to 300rpm, and treat for 20min.
[0043] In the present example, the preparation steps of the binder active component are as follows: Take 7.5g of the composite product, add 50ml of the mixed solvent, immediately adjust the magnetic stirring speed to 100rpm, treat for 5min, then increase the system temperature to 50℃, evacuate the air with nitrogen, add 0.5g of acrylic monomer and 0.3g of cerium nitrate to the system, then add 1.2ml of ethylenediaminetetraacetic acid with a mass concentration of 3% dropwise at a rate of 2ml / min, treat for 2h, then add 3g of acrylic monomer to the system, add 0.2g of methylene bisacrylamide and 0.15g of ammonium persulfate, adjust the temperature to 60℃, treat for 2.5h, then adjust the pH to 7 with 0.1mol / L sodium hydroxide solution, filter the precipitate, wash with water for 3 times, and dry in an oven at 35℃ for 3h to obtain the binder active component.
[0044] The composite product in the present example is prepared by Preparation Example 2.
[0045] The mixed solvent is obtained by mixing ethanol and acetic acid with a mass concentration of 0.5% in a volume ratio of 1:1.
[0046] Example 5 The difference between the present example and Example 1 is that the preparation steps of the binder active component are as follows: Take 7.5 g of the composite product, add 50 ml of mixed solvent, then adjust the magnetic stirring speed to 100 rpm, treat for 5 min, then raise the system temperature to 50°C, evacuate the air with nitrogen, add 0.5 g of acrylic monomer and 0.3 g of cerium ammonium nitrate to the system, then add 1.2 ml of 3% ethylenediaminetetraacetic acid at a rate of 2 ml / min, treat for 2 h, then add 3 g of acrylic monomer to the system, add 0.2 g of methylene bisacrylamide and 0.1 g of ammonium persulfate, adjust the temperature to 55°C, treat for 2 h, then adjust the pH to 7 with 0.1 mol / L sodium hydroxide solution, filter the precipitate, wash with water 3 times, then dry in an oven at 35°C for 3 h to obtain the binder active component.
[0047] The composite product in this example was prepared according to Preparation Example 3.
[0048] The mixed solvent was obtained by mixing ethanol and 0.5% acetic acid with a volume ratio of 1:1.
[0049] The remaining steps were the same as in Example 1.
[0050] Comparative Example 1 The difference between this comparative example and Example 1 was only in the preparation steps of the binder active component, which were as follows: Take 7.5 g of the composite product, mix with 6 g of polyacrylic acid to obtain the binder active component.
[0051] The polyacrylic acid (molecular weight 20000) was provided by Guangdong Wengjiang Chemical Reagent Co., Ltd.
[0052] The remaining steps were the same as in Example 1.
[0053] Comparative Example 2 The difference between this comparative example and Example 1 was only in the preparation steps of the binder for iron powder production, which were as follows: Take 15 g of water glass, 10 g of aluminum phosphate, 80 g of deionized water, 2 g of polyacrylamide, and 5 g of carboxymethyl cellulose sodium, adjust the magnetic stirring speed to 300 rpm, treat for 20 min, and then obtain.
[0054] The remaining steps were the same as in Example 1.
[0055] Performance test 1. SEM test Take the chitosan microspheres prepared in Example 2 and perform SEM scanning test, and the test results are shown in Figure 1 .
[0056] 2. Pellet strength test Preparation: The balling machine was used to adjust the linear pressure ratio to 5 t / cm, and the balling diameter was 20 ± 5 mm. The iron powder (average particle size of 20 microns) was used as the raw material for balling. The binder for iron powder production in Examples 1-5 and Comparative Examples 1-2 was added to the balling machine at an addition ratio of 1:75 (liquid material ratio), and the balling process was performed for 10 min. The prepared iron powder pellets were air-dried overnight under natural conditions to obtain the test samples.
[0057] 2.1 Pellet drop strength test The test samples of Examples 1-5 and Comparative Examples 1-2 were placed on a test bench with a steel plate at the bottom. The pellets were released from a height of 0.5 m to allow free fall. If breakage occurred after n times of falling, the drop strength of the ball was (n-1) times. The test was performed 5 times for the same group of test samples, and the test data were recorded. The test results are shown in Table 1. Figure 2
[0058] 2.2 Pellet compression strength test (1) Green pellet compression strength test: The compression strength tester was used to determine the compression strength of the test samples of Examples 1-5 and Comparative Examples 1-2 according to the test method of GB / T 14201-2018 "Determination of Cold Pellet Compression Strength for Blast Furnace and Direct Reduction". Each group of test samples was determined 5 times, and the compression strength test data were recorded. The average value was taken as the final data.
[0059] (2) Roasted pellet compression strength test: The test samples of Examples 1-5 and Comparative Examples 1-2 were placed in a tube furnace and protected by nitrogen gas. The temperature was controlled at 1250°C, and the roasting process was performed for 30 min. Then the temperature was programmed to decrease to room temperature, and the heating was stopped. The compression strength tester was used to determine the compression strength of the test samples after overnight at room temperature. Each group of test samples was determined 5 times, and the compression strength test data were recorded. The average value was taken as the final data.
[0060] The test results of (1) and (2) are shown in Table 2. Figure 3
[0061] Analysis of Example 2 and combination with Figure 1 It can be seen that the chitosan product prepared by using n-hexane as the oil phase and a chitosan dilute solution as the water phase component, and then cross-linking with epichlorohydrin, leaching and low-temperature centrifugation, has a spherical structure, and there are pores on the surface, which can provide a carrier for subsequent pre-liquid assembly.
[0062] Analysis of Examples 1-5 and Comparative Examples 1-2 and combination with Figure 2 and Figure 3 It can be seen that, in the strength attribute, the embodiment scheme shows obvious effect better than the comparative example scheme; in the drop and green ball compression strength test, the embodiment and comparative example scheme show the same change trend; wherein, the impact and compression resistance of the pellet of the comparative example 2 is the worst; this is because, in the binder formula used in the comparative example 2, the binding mainly relies on the gelation of sodium silicate initial hydrolysis and the capillary action of liquid phase film, and the force is relatively weak, and the cold-pressed pellet is not firmly bonded; while the polyacrylic acid chain of the embodiment scheme is combined with the cold-pressed pellet through physical entanglement and bonding effect, and the cold-pressed pellet prepared has better bonding effect; the comparative example 1 only through blending combination, the effect is not as good as the embodiment scheme. In the compression strength test of the sintered ball, the comparative example 1 appears the strength reverse descending trend, which is different from the change trend of the strength attribute of other test groups; this is because, after the test sample is treated by the pipe furnace high temperature, the organic component in the binder is decomposed, so that the binding effect is lost, and the comparative example 1 has high proportion of organic component, so that the compression strength of the sintered ball after heat treatment is the worst; while the active component of the binder in the embodiment scheme is combined in the early and late stages, so that even after heat treatment, the compression strength of the sintered ball is still better than that of the comparative example 2.
[0063] The embodiment 1-5 and the comparative example 1-2 are analyzed and combined Figure 2 and Figure 3 It can be seen that, in all test groups, the embodiment 2 scheme has the best effect, which meets the actual application requirements.
[0064] The specific embodiment is only an explanation of the present application, and is not a limitation of the present application. Those skilled in the art can make modifications to the embodiment without creative contribution after reading the specification, but as long as the modifications are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A binder for iron powder production, characterized in that: The binder is prepared by mixing the following raw materials in parts by weight: 50-70 parts of a binder active component, 20-30 parts of water, 5-8 parts of ammonium dihydrogen phosphate, and 3-5 parts of sodium carboxymethyl cellulose; wherein the preparation steps of the binder active component include the following: [S01] taking a pre-liquid, mixing it with chitosan microspheres, degassing under reduced pressure, then returning to normal pressure, letting it stand, taking the solid part, dispersing it with an oily sealing agent, then adding acid and stirring, letting it stand again, and centrifuging at low speed, taking the bottom precipitate, washing, and drying it to obtain a composite product; [S02] taking the composite product, adding a mixed solvent, dispersing, heating and purging with nitrogen, then adding acrylic acid monomer for the first time, adding a crosslinking agent, reacting, then adding acrylic acid monomer, initiating treatment, then adjusting the pH to 7, filtering the precipitate, washing with water, and drying to obtain the bonding active component; The preliquid is obtained by dissolving sodium silicate, aluminum silicate, borax and sodium hydroxide in water and then treating the solution.
2. The binder for iron powder production according to claim 1, characterized in that: In the step [S01], the preparation steps of chitosan microspheres include the following: taking a chitosan solution, treating it in a water bath, then adding n-hexane, treating it with high-speed shearing, then dripping epichlorohydrin with a mass concentration of 10%, reacting, and then leaching and low-temperature centrifugation to obtain chitosan microspheres.
3. The binder for iron powder production according to claim 2, characterized in that: The chitosan solution is prepared by mixing chitosan, deionized water and glacial acetic acid in a mass volume ratio of (0.8-1) g:100 ml:(0.5-0.7) ml; The volume ratio of the chitosan solution, n-hexane and epichlorohydrin with a mass concentration of 10% is 100: (70-80): (10-12); The high-speed shearing treatment operation is: adjusting the rotation speed to 5000-8000 rpm and treating for 15-25 minutes.
4. The binder for iron powder production according to claim 2, characterized in that: The leaching and low-temperature centrifugation treatment is as follows: adding anhydrous ethanol five times the volume of the chitosan solution to the solution, treating for 3-5 hours, then adjusting the temperature to 3-4°C, adjusting the centrifugal speed to 3000-5000 rpm, and treating for 10-20 minutes.
5. The binder for iron powder production according to claim 1, characterized in that: In the step [S01], the decompression degassing treatment is as follows: reducing the pressure of the container to 0.1-0.3 MPa, adjusting the magnetic stirring speed to 75 rpm, and treating for 3-4 hours.
6. The binder for iron powder production according to claim 1, characterized in that: In the step [S01], the oily sealing agent is prepared by mixing white mineral oil, n-hexanol and Tween-20 in a mass volume ratio of (40-50) ml:10 ml:(0.5-1) g.
7. The binder for iron powder production according to claim 1, characterized in that: In the step [S01], the acid addition and stirring treatment is as follows: adding 0.05 mol / L hydrochloric acid at a rate of 1-1.5 ml / min, adjusting the magnetic stirring speed to 50 rpm, stirring for 40-60 minutes, and then stopping the stirring.
8. The binder for iron powder production according to claim 1, characterized in that: In the step [S02], the mixed solvent is obtained by mixing ethanol and acetic acid with a mass concentration of 0.5% in a volume ratio of (0.5-1):
1.
9. The binder for iron powder production according to claim 1, characterized in that: In the step [S02], the cross-linking agent is obtained by mixing ammonium cerium nitrate and ethylenediaminetetraacetic acid with a mass concentration of 3% in a mass volume ratio of (0.2-0.3) g: (1-1.2) ml.
10. The binder for iron powder production according to claim 1, characterized in that: In the step [S02], the mass ratio of the composite product, the first added acrylic acid monomer and the additional added acrylic acid monomer is (10-15):1:(5-6).
Citation Information
Patent Citations
Iron ore powder pellet adhesive and application thereof
CN103937969A
Preparation method for iron powder cold-pressing pellet composite binder
CN105219956A
Composite binder and application thereof to powdered iron forming
CN105925795A
Composite metallurgical pellet binder, cold-pressed pellet containing composite metallurgical pellet binder and preparation method of cold-pressed pellet
CN111020182A
Catalyst for sulfuric acid production
CN120243004A